Father Absence in Pregnancy or During Childhood and Pubertal Development in Girls and Boys: A Population‐Based Cohort Study. Issue 4 (5th January 2021) - Gaml‐Sørensen, Anne; Brix, Nis; Ernst, Andreas; Lunddorf, Lea Lykke Harrits; Ramlau‐Hansen, Cecilia Høst
Abstract : This cohort study, including 15, 810 children born 2000–2003 in Denmark, aimed to investigate the association between father absence in pregnancy or during childhood and pubertal development in girls and boys. The children were followed from 11 years of age and throughout pubertal development. Mean age differences according to exposure groups were estimated for each pubertal marker separately and for a combined pubertal marker. The results suggested that father absence in pregnancy and during childhood was associated with earlier pubertal development in girls, and father absence from late childhood was associated with earlier pubertal development in boys. The paternal investment theory, the psychosocial acceleration theory and the energetics theory were explored, and did not seem to explain the observed associations.